EVALUATION OF THE IMPLEMENTATION OF THE INSTITUTIONAL ACCOUNTING AND FINANCE SKILLS COMPETENCY TEST PROGRAM - SETYOWATI, Elis; MULJONO, Hery; FETRIMEN, Fetrimen (Journal of Education and Leadership in Education, 2023)
The purpose of this study was to determine the success and follow-up of the Competency Certification Test Program on Accounting and Financial Skills Competency for Institutions at Yapimda Vocational High School, Jakarta. This research was carried out at Yapimda Vocational High School, Jakarta, on the Competency of Accounting and Institutional Finance skills. This study uses the CIPP Descriptive Evaluative Model Research Method (Context, Input, Process, Product). The samples for this study were taken using the Purposive Sampling Technique, namely school principals, deputy principals, supervisors, LSP heads, heads of Institutional Accounting and Finance competencies, productive Accounting and Institutional Finance teachers, assessors of Institutional Accounting and Finance competencies, and students majoring in Institutional Accounting and Finance. Data collection techniques are interviews, observation and documentation. The results of the study show: 1) Evaluation of the context in the implementation of the USK Program in terms of environmental conditions is high, this aspect includes (a) Vision, Mission and Objectives of the School and LSP, (b) Policy regarding USK, 2) Evaluation of USK program input is classified as very high. This aspect includes (a) availability of facilities and infrastructure, (b) human resources, (c) USK planning, and (d) USK committee. 3) Evaluation of the process is classified as high, aspects that are assessed regarding the implementation of the USK program and 4) product aspects obtained are in the form of Competency Certificates.